(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Considera soil sample in contact with a porous ceramic membrane that allows the passageof the soil solution but not the soil particles. This plate is connected to aburette with a flexible water filled tube, and the height of the burette isadjusted so that the water level is at the same level as the soil surface. Inthis state, the soil will be saturated under equilibrium conditions.